POLITENESS STRATEGIES AND PRAGMATIC ERRORS IN MACHINE TRANSLATION SYSTEMS (Ustozlar uchun, 2026)
The article discusses the proposed classifications for analyzing translation performed by automatic translation systems and some of their limitations. Material related primarily to translations in pairs with the Uzbek language and performed with with the help of the most popular machine translation services "Yandex Translator," "Google Translate" and "Promt." In particular, the main classes of errors highlighted by various authors, their frequency, as well as their "weight" in terms of their ability to reduce to communication failure. Currently absent the time of a unified approach to constructing such classifications, as well as dependence of existing typologies on the type of text, language pair and specific automatic translation system.